A case study: the description of colonialism in the Enciclopedia del Ragazzo italiano (1938-1949) - Domenico Francesco Antonio Elia (University of Bologna, 2023)
The paper investigates how the history of the colonial period was narrated in parascholastic materials that complemented school textbooks after the Second World War. The author focuses on the Enciclopedia del Ragazzo Italiano published in Milan by Giuseppe Latronico (1896-1981) with Labor publisher between 1938 and 1940. By analysing the paragraphs dealing with colonialism, the author delineates continuities and changes between the first edition, which appeared during the period of State-sponsored racism, and the 1949 one. The paper shows how Italian colonial imagery continued after the Second World War when Italians avoided any public reflection on African independence movements. The lack of public debate on colonialism resulted in the persistence of long-lasting cultural constructions that dated back to 19th-century military operations conducted in Africa.